Diabetic ketoacidosis at diagnosis of type 1 diabetes mellitus in Malaysian children and adolescents - Mohamad Adam Bujang; Janet Hong Yeow Hua; Muhammad Yazid Jalaludin; Fuziah Md Zain; Loo Ling Wu (Malaysian Family Physician, 2015)
Type 1 diabetes mellitus (DM) accounts for more than 90% of childhood and adolescent diabetes. Of the estimated 479,600 type 1 diabetic children worldwide, 24% were from the South-East Asian region and 6.4% from the Western Pacific region.2–3 The annual incidence for childhood type 1 DM (0–14 year age group) ranged from 0.1 per 100,000 in China to 57.6 per 100,000 in Finland.3–5 The incidence of type 1 DM appeared to be low in the Western Pacific region with the exception of Australia and New Zealand. In Malaysia, type 1 DM was estimated to account for 69.2% of children and adolescents with diabetes.